2021 Financial Sector Assessment Program Review : Background Paper On Traction. (Policy Papers; Policy Paper ;, 2021)
A key criterion for judging the success of the Financial Sector Assessment Program (FSAP) is the extent to which the program has enhanced the IMF's engagement with policymakers and influenced country policies. This reflects the fact that achieving one of the program's key objectives-reducing the frequency and severity of financial crises-rests on its ability to encourage policy action by country authorities, either directly or through other bilateral and multilateral activities. The 'traction' of FSAPs thus reflects the degree to which the program is seen as useful by the authorities and the effect it has in shaping the domestic policy agenda. And the impact that the FSAP may have on wider domestic and international audiences.